Applying Conversation Method and Self-Confidence and Its Effect to Learning Achievement - Imam Kholis Sagita (Journal Corner of Education, Linguistics, and Literature, 2021)
English in elementary schools in the implementation of learning is still not effective until now. Actually, there are many problems related to the implementation of the development of English learning. In fact, the development of learning English itself is very beneficial for elementary school students, so they can improve their abilities. The research method used in this classroom action research is an experimental method with a Factorial Group Design (FGD) design with 2 categories. The data analysis technique in this study used two way ANOVA, with the help of computers, namely: SPSS for Windows version 24 program. The results of the study can be concluded that there are differences in English learning outcomes between learning by conversation methods and conventional methods for grade 4 students. Madrasah Ibtidaiyah Nu Sumber Agung. Then, there is no difference in English learning outcomes between grade 4 students of Madrasah Ibtidaiyah Nu Sumber Agung with high self-confidence and low self-confidence. And the last, there is no interaction of methods with self-confidence on learning achievement in English.